Challenges and associated factors of being a Nursing Officer in the Teaching Hospital Jaffna - Hajeekaran, L.; Keerthika, Y.; Kavindu Hansaka, M.A.W.; Uvashri, T.; Thayashakhary, A.; Kumarendran, B.; Sivayokan, S. (University of Jaffna, 2024)
Background and objectives: Nurses provide patient care, educate the patients and their families, and act as important liaisons between patients and doctors. The objective of this study was to determine the challenges and associated factors of being a nursing officer at Teaching Hospital Jaffna. Methods: A population-based cross-sectional analytical study was carried out among 427 nursing officers in Teaching Hospital Jaffna using stratified sampling to recruit the participants from February 2022 to October 2023 using a self-administered questionnaire and analyzed with SPSS. Challenges were defined as limitations and demands common to the nursing field, and included perceived stress level, job satisfaction, mental well- being and work-family balance. We used the Perceived Stress Scale (PSS), and adapted the Minnesota Satisfaction Questionnaire, PHQ -9 for Mental Wellbeing, and a section of the Work Life Balance questionnaire. The significance of association was determined using Chi-square test, one-way ANOVA and t-test with the level of significance set at 0.05. Results: The response rate was 100.9% (431/427), it was oversampled. Among participants, 24.4% (n=105) were male and 75.6% (n=326) were female. Majority of the participants were Tamil 60.1% (n=259) and mean age was 32.09 years. The majority were in the moderate stress level (81.9%, n=353). There was an association between perceived stress level and age (p<0.001) and having children (p=0.007). There was an association between job satisfaction and perceived stress level (p=0.01). Job satisfaction was associated with first language (95% CI: 0.18 to 1.56, p=0.014) and hometown (p=0.03). The majority of participants were in the mild depression grading of the PHQ- 9 scale (38.5%, n=166). State of mental well-being was associated with marital status (p<0.001) and sex (p<0.001). The work-family balance was associated with sex (95% CI: -1.28 to -0.28, p=0.003) and number of night shifts per week (95% CI: 9.7 to 10.09, p=0.03). Conclusion and recommendations: There was an association among the challenges especially between job satisfaction and perceived stress. Strategies should be developed considering the mental health of nursing officers such as awareness programmes and recreational activities. Policies should be implemented at administrative level considering the problems.
Keywords: Nursing officer; Perceived stress; Job satisfaction; Mental well-being; Work- family balance